PENGARUH SOSIAL MEDIA YOUTUBE TERHADAP PERILAKU LITERASI SISWA SMA HUTAMA - Nala Prasasta Jati; Zainal Abidin; Mickey Oxcygentri (Linimasa : Jurnal Ilmu Komunikasi, 2022)
This study aims to determine how much partial and simultaneous influence on intensity, and message content on literacy behavior at Hutama High School. This study uses quantitative methods with descriptive analysis and uses a qualitative approach. Data analysis was carried out by assessing how much influence the independent variable, namely the intensity and content of the message, had on the dependent variable, namely literacy behavior by using the dimensions and indicators of each variable. The results showed that the intensity and content of the message had a simultaneous effect on literacy behavior with an Fcount value of 50,130 with a significant value of 0.00 with the meaning that H0 was rejected and H2 was accepted. In this case the research was conducted using multiple regression analysis. The results of this study indicate that there is an influence and relationship from the Youtube social media platform on Literacy Behavior which is known from the R value.